The relationship among lead knee extension, fastball velocity and elbow torque in professional baseball pitchers - Dowling, B.; Manzi, J. E.; Raab, G.; Coladonato, C.; Dines, J. S.; Fleisig, G. S. (Sports Biomechanics, 2022)
The purpose of this study was to investigate potential differences in lead knee extension velocity, elbow varus torque and lead knee extension (the change in lead knee flexion from foot contact to ball release) in high and low velocity professional pitchers. Three-dimensional motion capture (480 Hz) was used to assess 322 professional pitchers. T-test were used to compare the two groups and multiple linear regression analyses were performed on all pitchers (n = 322). The high-velocity group (n = 99; 40.3 ± 0.9m/s) had greater lead knee extension (17 ± 13 vs 5 ± 14°, p < 0.001, g = 0.9), lead knee extension velocity (419 ± 135 vs 297 ± 121°/s, p < 0.001, g = 0.9) and elbow varus torque (91.1 ± 15.5 vs 84.0 ± 14.7 Nm, p < 0.001, g = 0.5) compared to the low-velocity group (n = 88; 36.1 ± 1.2 m/s). Lead knee extension (R2 = 0.352, p < 0.001) and lead knee extension velocity (R2 = 0.326, p < 0.001) were found to be positive predictors of ball velocity but not elbow varus torque (p = 0.807). Instructing professional pitchers to utilise a lead leg bracing technique that facilitates increased lead knee extension can contribute to faster ball velocity, but most likely results from a combination of other mechanics.